Reconstructing 3D model from single image - Kumar, Nikita. (2011)
The rapid development in the fields of virtual reality and electronic game caused relentless increase in demand for 3D models. The ability to perform fast and accurate 3D reconstruction of an environment or object is central to many areas of computer vision processing. One of the main problems of 3D model creation is the lack of proper image input as well as the complexity in using professional 3D software to generate these models.